Prevalence of anxiety and self-medication in medical students - Raissa Carvalho de Oliveira; Yasmin Gabrielly Pereira do Nascimento; Isaú Flávio Coutinho Pereira; Matheus Malta Coimbra; Camila Holanda de Sousa; Cândido Víctor Pereira Oliveira; Renandro de Carvalho Reis (Universidade Estadual de Maringá, 2024)
Anxiety is a natural and fundamental reaction of self-preservation. But in excessive amounts, to the point of significantly affecting the individual's life, it is pathological and may lead to the practice of self-medication, which, in turn, may represent damage to health. Due to some reasons, such as intense stress, and long study hours, many medical students are more likely to develop psychiatric disorders, such as anxiety. The present study aimed to analyze the prevalence of anxiety and self-medication in medical students at a higher education institution. The study was carried out in a higher education institution in Teresina, state of Piauí, in April and May 2022. The target audience was a group of medical students from the first to the twelfth period. They were given electronic forms via instant messaging application, containing the Beck Anxiety Inventory, sociodemographic (with reports of self-medication), and academic questionnaires. The responses were processed by the statistical software 'Statistical Package for the Social Sciences' (SPSS) 20.0 to run a chi-square correlation. The results showed that 86% students were aged 16 - 26 and were in the basic cycle. The female participants showed a greater correlation with cases of anxiety, which may be related to hormonal factors that usually start at puberty. As for self-medication, 64% students answered that they do not practice it, which differs from several studies. Therefore, women had a greater correlation with anxiety, probably due to physiological and environmental stimuli. Self-medication did not influence a correlation with cases of anxiety.